REMEDIES FOR SEWING MACHINE MALFUNCTIONS TASHKENT INSTITUTE OF TEXTILE AND LIGHT INDUSTRY - Palvannazirova Nasiba; Butovskiy P. M. (American Journals Publishing, 2024)
This paper provides an overview of modern embroidery machines, focusing on their digital design, automation, and stitch variety. It also explores the various applications of embroidery devices, such as fashion, interiors, gifts, and hobbies.